Fruit and Seed Production of Mahoni (Swietenia macrophylla King) at Various Crown Dimention and Leaf Stomata Condition - Kurniawati Purwaka Putri; Agus Astho Pramono; Dida Syamsuwida (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2018)
Seed and fruit production are strong related to the process of plant photosynthesis and leaves are the main organ in the photosynthesis process. All leaves characteristics such as morphology (leaf surface area), anatomy (stomata index and density) and physiology greatly influence organic compounds (assimilates) produced from photosynthesis. The aim of the study was to determine the effect of canopy width, stomata index and density, and leaf area on the production of fruit and seed of mahogany (Swietenia macrophylla). The study was carried out on a 21-years-old mahogany seed stand in Forest Research of Parungpanjang. The experimental design used was a completely randomized design with canopy diameter, leaf area, stomata density and stomata index as a treatments. Each treatment consists of 5 (five) classification levels. The result showed that fruit and seed production were affected by canopy diameter of the tree. Leaf area, stomata density and stomata index did not influence the production of produced fruit.